2019
DOI: 10.1364/jocn.11.000478
|View full text |Cite
|
Sign up to set email alerts
|

Robust network design for IP/optical backbones

Abstract: Recently, Internet service providers (ISPs) have gained increased flexibility in how they configure their in-ground optical fiber into an IP network. This greater control has been made possible by (i) the maturation of software defined networking (SDN), and (ii) improvements in optical switching technology. Whereas traditionally, at network design time, each IP link was assigned a fixed optical path and bandwidth, modern colorless and directionless Reconfigurable Optical Add/Drop Multiplexers (CD ROADMs) allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…As a result, network operations changed and the optical backbone layer no longer performed any failure restoration rerouting activities. Only the IP traffic layer network performed rerouting to account for network failures [35, 54]. There were several reasons for this change: For telephone traffic networks, the nodes (switches) are extremely reliable [6] and normal restoration planning does not need to account for node failures.…”
Section: Backbone Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, network operations changed and the optical backbone layer no longer performed any failure restoration rerouting activities. Only the IP traffic layer network performed rerouting to account for network failures [35, 54]. There were several reasons for this change: For telephone traffic networks, the nodes (switches) are extremely reliable [6] and normal restoration planning does not need to account for node failures.…”
Section: Backbone Networkmentioning
confidence: 99%
“…During the IP traffic era, network engineers concluded that it was not cost effective to perform backbone layer network restoration. In fact, some new optical network capabilities could make backbone layer restoration more attractive again [54].…”
Section: Backbone Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Today's service providers cope with the loss of capacity caused by fiber cut events by over-provisioning the network. In particular, to protect from massive packet loss, WAN operators preallocate extra capacity for failover paths using (𝑖) failure-aware Traffic Engineering (TE) [17,40,48,63,79] and (𝑖𝑖) optical path protection [14,19,59,68,80,81,84]. In such techniques, when fiber cuts occur, traffic is automatically shifted from failed IP links to pre-allocated backup paths.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [131] presented an ILP and designed an efficient heuristic that solves the equipment placement problem in network design, determines the optimal mapping of IP links to the optical infrastructure for any given failure scenario and determines the best route for the offered traffic over an IP topology. Experiments showed that the proposed ILP offers cost savings of up to 29% compared to traditional network design techniques.…”
Section: Survivable and Fault-tolerant Backbone Networkmentioning
confidence: 99%